A novel monoclinic metal oxide catalyst for oxygen evolution reactions in alkaline media. Issue 5 (28th January 2022) - Qian, Yang; Xu, Xianlun; He, Yi; Lei, Lecheng; Xia, Yanghong; Zhang, Xingwang
Abstract : Co-Doped Fe2 (MoO4 )3 was synthesised via spray pyrolysis-calcination. The optimal Co0.15 -Fe2 (MoO4 )3 exhibited excellent OER performance with an overpotential of 273 mV at 10 mA cm −2 . Abstract : The main bottleneck of electrolytic water for hydrogen production in alkaline media is the oxygen evolution reaction (OER) involving four-electron transfer. Designing highly efficient OER catalysts is attractive to accelerate this process. Monoclinic oxides have gained enormous interest as promising candidates for electrocatalysis due to their low cost and abundant storage. The introduction of transition metals into metal oxides to tune the electronic structure of active sites is regarded as one of the promising methods for enhancing OER performance. Herein, we designed a Fe2 (MoO4 )3 catalyst by a spray pyrolysis strategy and enhanced the OER performance of Fe2 (MoO4 )3 with Co doping, which displayed a low overpotential of 273 mV to drive 10 mA cm 2 . The octahedral Fe site engineering leads to higher reaction kinetics and more active site exposure. Density functional theory (DFT) calculations further revealed that the introduction of Co can reduce the energy barrier for the OER process and weaken the absorption of *–O. This work provides a new insight into the fabrication of monoclinic oxide electrocatalysts for OERs in alkaline media.